1988
DOI: 10.1016/0035-9203(88)90536-6
|View full text |Cite
|
Sign up to set email alerts
|

Absence of viraemia in cattle after experimental infection with Japanese encephalitis virus

Abstract: Cow calves were infected with Japanese encephalitis virus (JEV) by parenteral inoculation. One batch was reinfected with JEV, followed by West Nile virus (WNV), while another batch was reinfected directly with WNV. No viraemia due to either JEV or WNV was demonstrated in any of the calves. Culex tritaeniorhynchus mosquitoes fed on 4 of the calves infected with JEV during the first 10 d had no detectable virus, nor did they transmit the virus by bite to susceptible baby chickens. In another experiment, calves d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…28 Cattle do not produce sufficient levels of viremia to act as amplifying hosts, and may even help to reduce JE transmission in some areas. [29][30][31] Further studies in the Torres Strait and Cape York Peninsula are required to determine the effects of mosquito host feeding patterns on JE transmission. The timing of mosquito trapping for virus isolation during the cycle of pig and/or ardeid bird and mosquito infection is critical.…”
Section: Resultsmentioning
confidence: 99%
“…28 Cattle do not produce sufficient levels of viremia to act as amplifying hosts, and may even help to reduce JE transmission in some areas. [29][30][31] Further studies in the Torres Strait and Cape York Peninsula are required to determine the effects of mosquito host feeding patterns on JE transmission. The timing of mosquito trapping for virus isolation during the cycle of pig and/or ardeid bird and mosquito infection is critical.…”
Section: Resultsmentioning
confidence: 99%
“…Although our data clearly indicated that in the calf's case the causative agent was JEV, it remains unclear why the calf developed the disease, since cattle usually have undetectable or no viremias after JEV infection (22,23). Among humans, children are at high risk for a fatal outcome of JE (24), and the age of the calf may have contributed to the outcome in this case, but the number of bovine JE cases is quite low and seems not to be enough to discuss the age dependency of JE in cattle (16,20,21).…”
mentioning
confidence: 78%
“…Among the five genotypes of JEV based on the sequence of the E region, which encodes envelope protein (17), the dominant genotype shifted from 3 to 1 in Japan in the mid-1990s (3,8,18,19). It is thus thought to be JEV genotype 3 (G3) that caused natural infection in cattle or was used for an experimental infection of calves in the 1940 to 1950s (20)(21)(22), and it was also the G3 P20778 strain which was used for an experimental infection of cattle in India (23). A natural case of JE in an 18-month-old cow was reported in Chiba Prefecture, Japan, in 1996 (16), and JEV was isolated from the affected cow in this case; however, there has been no report that described the genotype of the isolate.…”
mentioning
confidence: 99%
“…Japanese encephalitis viruses were not only isolated from pigpens but also from a cattle shed. Because JEV is not known to cause viremia in cattle, 23,24 mosquitoes harboring JEV might have flown from other places, such as a pigpen 2 km away, to this shed. The fact that antibody nor JEV was not detected in seven cattle less than one year of age in 2009 supports the above hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report, cattle acquired antibody after experimental infection with JEV. 24 Because Cx. tritaeniorhynchus mosquitoes were few in number in 2009 ( Figure 3A ), there might have been little opportunity for the infection of cattle.…”
Section: Discussionmentioning
confidence: 99%